Value Positioning Advantage: A Resource Advantage Theory of Competition Perspective - Salsabila, Cika Tania; Ferdinand, Augusty Tae (Universitas Multi Data Palembang, 2025)
This study aims to bridge previous inconsistent research regarding the role of social media marketing on business performance. The design in this study is applied with a quantitative approach. The theoretical model was tested on 200 samples of Coffeeshop businesses in Semarang City, Indonesia. Data analysis was carried out with AMOS software. The novelty of this study lies in the variables and indicators that are deduced from the resource advantage theory of competition. We combine simple mediation effect testing that produces destination competitiveness to be a good intermediary in the influence of social media marketing on business performance. The rejection of the two hypotheses leaves a gap for future studies to be able to be explored further.